Studying the Relationship Between Health Literacy and Health Behaviors 3E.2S. of the Elderly at Risk for Hypertension Ban Hua Den Subdistrict Health Promoting Hospital, Bang Khut Subdistrict, Sankhaburi District Chainat Province - Aungkab, Chonticha; Kayadee, Ajcharapan; Watthana, Sasima; Siengnan, Saowalak (Journal of Preventive Medicine Association of Thailand, 2024)
Objectives: This research was to study the relationship between health literacy and the 3E.2S. healthcare behavior of the elderly at risk of Hypertension in Ban Hua Den Subdistrict Health Promoting Hospital. Methods: This study used Nutbeam's framework of health literacy as a guideline for the study. The sample group selected by simple random sampling of 176 elderly people at risk of hypertension aged 60 years and over. using a questionnaire regarding general characteristics, health literacy, knowledge about hypertension, and self-care behavior related to hypertension. Data were analyzed using descriptive statistics and Pearson correlation statistics. Results: Showed that the health literacy of sample had a low level and health behavior had a moderate level. The research results found that there is a relationship between health literacy and health behavior, according to the principles of 3E.2S. This study yielded statistically significant outcomes (p < .01) expect for decision making. Conclusion: Health literacy is important for self-care behavior. Health teams should find methods to develop health literacy among the elderly at risk Hypertension. To be able to use knowledge judiciously in selecting self-care behaviors so that high blood pressure can be properly controlled.